United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of the Depository Trust Company's Observance of the CPSS-IOSCO Recommendations for Securities Settlement Systems. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of the Depository Trust Company's Observance of the Committee on Payment and Settlement Systems/International Organization of Securities Commissions (CPSS-IOSCO) Recommendations for Securities Settlement Systems for the United States. The assessment reveals that the legal framework provides a high degree of legal assurance that transactions are enforceable. The membership agreement into which participants enter is enforceable under New York State law. The assessment recommends that securities settlement systems should have a well-founded, clear, and transparent legal basis in the relevant jurisdictions.